Evaluation of neoadjuvant immunotherapy in resectable gastric/gastroesophageal junction tumors: a meta-analysis and systematic review - Wang, Jincheng; Tong, Ti; Zhang, Guangxin; Jin, Chengyan; Guo, Haiping; Liu, Xueying; Zhang, Zhengxiao; Li, Jindong; Zhao, Yinghao (Frontiers in Immunology, 2024)
Neoadjuvant therapy for resectable gastric cancer/gastroesophageal junction tumors is progressing slowly. Although immunotherapy for advanced gastric cancer/gastroesophageal junction tumors has made great progress, the efficacy and safety of neoadjuvant immunotherapy for locally resectable gastric cancer/gastroesophageal junction tumors have not been clearly demonstrated. Here, we conducted a systematic review and meta-analysis to assess the efficacy and safety of neoadjuvant immunotherapy and advance the current research.Methods: Original articles describing the safety and efficacy of neoadjuvant immunotherapy for resectable gastric cancer/gastroesophageal junction tumors published up until October 15, 2023 were retrieved from PubMed, Embase, the Cochrane Library, and other major databases. The odds ratios (OR) and 95% confidence intervals (CIs) were calculated for heterogeneity and subgroup analysis.Results: A total of 1074 patients from 33 studies were included. The effectiveness of neoadjuvant immunotherapy was mainly evaluated using pathological complete remission (PCR), major pathological remission (MPR), and tumor regression grade (TRG). Among the included patients, 1015 underwent surgical treatment and 847 achieved R0 resection. Of the patients treated with neoadjuvant immunotherapy, 24% (95% CI: 19%-28%) achieved PCR and 49% (95% CI: 38%-61%) achieved MPR. Safety was assessed by a surgical resection rate of 0.89 (95% CI: 85%-93%), incidence of ≥ 3 treatment-related adverse events (TRAEs) of 28% (95% CI: 17%-40%), and incidence of ≥ 3 immune-related adverse events (irAEs) of 19% (95% CI: 11%-27%).Neoadjuvant immunotherapy, especially neoadjuvant dual-immunotherapy combinations, is effective and safe for resectable gastric/gastroesophageal junction tumors in the short term. Nevertheless, further multicenter randomized trials are required to demonstrate which combination model is more beneficial.